Implementasi Kepemimpinan Kepala Sekolah dalam Pendidikan Karakter (Studi Kasus Di SMP Negeri 2 Pammana) - Riska Ramayana; Muhammad Arafah; Besse Herlina; Rizal Irfandi (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research discusses the implementation of school principal leadership in character education. The method used is a library research approach. Literature study involves collecting data, reading, taking notes, and processing research materials. Based on data and research results conducted by researchers, the Implementation of Principal Leadership in Character Education at SMP Negeri 2 Pammana is implemented as follows: firmness and discipline, the leadership role of the principal as a motivator, creating a conducive school climate and culture; and the example of the school principal. The conclusion is that character formation is the development of knowledge and action. Keywords: Implementation, Leadership, and Character Education